My lovely wife - Downing, Samantha (Berkley, 2019)
Our love story is simple. I met a gorgeous woman. We fell in love. We had kids. We moved to the suburbs. We told each other our biggest dreams, and our darkest secrets. And then we got bored. We look like a normal couple. We're your neighbors, the parents of your kid's friend, the acquaintances you keep meaning to get dinner with. We all have our secrets to keeping a marriage alive. Ours just happens to be getting away with murder.